2004
DOI: 10.1111/j.1365-2133.2004.06168.x
|View full text |Cite
|
Sign up to set email alerts
|

Perforin expression is upregulated in the epidermis of psoriatic lesions

Abstract: Perforin expression is upregulated in the epidermis of psoriatic lesions, suggesting a potential role for perforin in the creation of the psoriatic plaque.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 18 publications
4
28
0
1
Order By: Relevance
“…In our previous work [8] we demonstrated the up-regulation of perforin expression in peripheral blood lymphocytes in exacerbation phase of disease compared to healthy individuals, what was also proved by others as well [10]. A higher expression of this cytolytic molecule was also detected in lesional psoriatic skin compared to unlesional and healthy skin [9,11,12]. Thus, it was obvious that perforin molecule might play a certain role in blood and lesions of psoriatic patients, but possible oscillations in its expression as well as its effect related to disease severity was not as yet investigated.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In our previous work [8] we demonstrated the up-regulation of perforin expression in peripheral blood lymphocytes in exacerbation phase of disease compared to healthy individuals, what was also proved by others as well [10]. A higher expression of this cytolytic molecule was also detected in lesional psoriatic skin compared to unlesional and healthy skin [9,11,12]. Thus, it was obvious that perforin molecule might play a certain role in blood and lesions of psoriatic patients, but possible oscillations in its expression as well as its effect related to disease severity was not as yet investigated.…”
Section: Discussionsupporting
confidence: 79%
“…As we have previously demonstrated [9], as well as demonstrated by Yawalkar et al [11,12], a significant infiltration of perforin+ cells mainly of CD8 phenotype was present in dermis, epidermis and throughout dermoepidermal junction of psoriatic plaque. Despite our expectations, we have not found a significant difference in percentage of perforin+ cells between a psoriatic plaque of severely and mildly affected patients.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Additionally, psoriatic NK cells might have increased cytotoxicity through the release of cytotoxic granules such as perforin, which were found upregulated in the psoriatic lesions. 87 Recently, NKT cells have been demonstrated to be a potent IL-17 producer, suggesting that these cells may act similarly as dermal cd T cells in psoriasis pathogenesis. 88 In addition to these unconventional T cells, Lin et al 89 reported that mast cells and neutrophils were prominent cells that produced IL-17 in the skin of healthy controls as well as psoriasis patients.…”
Section: Innate Immune T Cells or Innate Effector Cells In Psoriasis mentioning
confidence: 99%
“…84,85 Both NK and NKT cells infiltrations have been found significantly increased in psoriatic lesions. 86,87 Infiltrating NK cells express CXCR3, CCR5 and CCR6 as well, which are in response to the corresponding chemokines CXCL10, CCL5 or CCL20 secreted by keratinocytes. Additionally, psoriatic NK cells might have increased cytotoxicity through the release of cytotoxic granules such as perforin, which were found upregulated in the psoriatic lesions.…”
Section: Innate Immune T Cells or Innate Effector Cells In Psoriasis mentioning
confidence: 99%